170k views
2 votes
If f(x) = x^4 + 3x^3 – x^2 + 6, find f(-3). A) -3 B) -2 C) 2 D) 3

User Marquito
by
5.1k points

2 Answers

3 votes

Answer:

f [0] = 6

Explanation:

f [x] = x ^ 4 plus 3 x ^ 3 - 0 ^ 2 plus 6

f [0] = 0 plus 3 x 0 - 0 plus 6

f [0] = 0 plus 6

f [0] = 6

User Michel Keijzers
by
5.2k points
5 votes

Answer:

f(-3) = -3

Explanation:

replace x with -3 and solve

(-3)^4 = 81

3(-3)^3 = -81

(-3)^2 = 9

6 = 6

now solve

x^4 + 3x^3 – x^2 + 6

81 + (-81) - 9 + 6

-9 + 6

-3

User Mralexlau
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.